Entrepreneurial Leadership As A Catalyst For Human Capital Development: A Systematic Literature Review - Arianti Anaya; Yunia Wardi; Susi Evanita; Hendrik Heri Sandi (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2026)
Human capital development has become a strategic priority for organizations, including healthcare institutions, facing rapid digital transformation, workforce shortages, and increasing demands for innovation and service quality. Entrepreneurial leadership has been recognized as a leadership approach capable of fostering workforce competencies, talent retention, and organizational innovation. This systematic literature review aims to synthesize empirical and theoretical evidence regarding the role of entrepreneurial leadership in human capital development. Following PRISMA 2020 guidelines, literature was identified from Scopus, ScienceDirect, SpringerLink, Emerald Insight, Google Scholar, and complementary citation chaining procedures. From 501 identified records, 50 highly relevant studies were included for thematic synthesis. The findings reveal that entrepreneurial leadership enhances workforce skills through continuous learning, coaching, and competency development; improves talent retention through affective commitment and supportive organizational climates; and strengthens innovation performance through intellectual capital and dynamic capabilities. Digital transformation, Industry 4.0, artificial intelligence, and sustainability frameworks emerged as important contextual factors influencing leadership effectiveness. In healthcare organizations, these findings suggest that entrepreneurial leadership can support workforce resilience, digital competency development, service innovation, and sustainable healthcare performance. Despite conceptual and methodological limitations within the literature, entrepreneurial leadership remains a promising approach for strengthening human capital development in increasingly complex organizational environments.